(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2021)
In this paper, it presents a detailed analysis of the use of the parabolic solar cooker in cooking and boiling water. Three models of parabolic solar cookers were manufactured with aperture diameter (96 cm, 120 cm, and 140 cm) made using satellite dishes of the same diameters and using glossy aluminum foil as a reflector sun ray after being cut into strips 10 cm wide and glued to the inner surface of the dish. A metal tin can (3L) was used as an absorbent receiver instead of a cooking pot. Experiments were conducted to boil water from the roof of the house in Nasiriyah City located in southern Iraq. Through this study, the optical efficiency of the three types of parabolic solar cookers with diameters (96,120, and 140 cm) was calculated, as they were (69,66%), (66.5, 66.35%), and (67.4,66.7%) respectively. The amount of heat gained for the three cookers, respectively (670.665, 556.394W), (1142.6, 1074.83 Watt), and (1535.38, 1460 Watt). The heat loss from the receiver, respectively (68.6, 70.53 W), (118.16, 140.385 W), and (112.69, 96.576 W). The collector efficiency of the three cookers (58.77, 53.32%), (56.16, 53.3%), and (60, 60%), and the cooking power of these cookers (475,875, 264.375 W), (413.8, 434.13 W). ), (740.25, 691.44 W). Many tests were conducted on the specified location at the weather in Iraq during the winter season. The results of the experiments showed that the parameters of the solar cooker mentioned above mainly depend on the diameter of the concentrator dish, the quality of the reflector used, the cooking time, and the closing to midday. While the high ambient air speed leads to a decrease in the pot temperature by increasing the heat loses to the surrounding air through convection, thus greatly affected the solar cooker parameters, especially the collector efficiency and cooking power, as well as the accuracy of directing the dish towards the sun, and determining the focus accurately affected on the parameters of the solar cooker too